#TITLE_ALTERNATIVE# - (NIM: 13206151); Pembimbing : Dr. Achmad Munir, HERMANTO
In broadband communication such as WiFi and WiMAX, the antenna which has broadside radiation pattern is required. One of antenna types that has broadside radiation pattern is a bifilar helical antenna (BHA) operates in normal mode. This final project focuses on designing a novel normal mode BHA for 3.3 GHz WiMAX application, which is including the determination of BHA dimension, impedance matching, and balancing unit (balun) using microstrip. The BHA is made of a copper conductor wire that has diameter of 1 mm and uses 2 numbers of its turns with pitch distance of each turns is 25.80 mm, so the total height is 52.60 mm. The diameter of BHA used is 8.68 mm as of its circumference (C) that is 0.3 λ. The antenna is then fed by a 50 Ω coaxial type terminal and using a microstrip line for its balun as well as matching impedance. A double side FR-4 Epoxy substrate with total size 15 cm x 15 cm is used where the microstrip line is etched on the top side whilst the other side is applied for its ground plane. With this structure, it can produce bandwidth about 230 MHz at 10 dB Return Loss, Gain about 6.02 dBi, and a broadside radiation pattern to operate in 3.3 GHz. This can be an advantage to implement this type of antenna because of its small size which can decrease cost of implementation.